Element Analysis Based on Energy-Dispersive X-Ray Fluorescence - Min Yao; Dongyue Wang; Min Zhao (Advances in Materials Science and Engineering)
Energy-dispersive X-ray fluorescence (EDXRF) spectrometry is a nondestructive, rapid, multielement, highly accurate, and environment friendly analysis compared with other elemental detection methods. Thus, EDXRF spectrometry is applicable for production quality control, ecological environment monitoring, geological surveying, food inspection, and heritage analysis, among others. A hardware platform for the EDXRF spectrometer is designed in this study based on the theoretical analysis of energy-dispersive X-ray. The platform includes a power supply subsystem, an optical subsystem, a control subsystem, and a personal computer. A fluorescence spectrum analytical method is then developed to obtain the category and content of elements in a sample. This method includes qualitative and quantitative analyses. Finally, a series of experiments is performed. Results show that the precision of the proposed measurement method is below 8%, whereas its repeatability is below 2%.